Effect of Urea and Humic acid fertilization on some chemical/physical Properties and yield of cow pea Vigna unguiculata (L.) walp - Mohammed AL-Kaaby (University of Thi-Qar Journal of Science, 2019)
This study was conducted in AL-Qaraf region, Thi-Qar province, to study the effect of earth fertilization byUrea and Humic acid on some chemical/physical properties and yield of cow pea. A local cultivar of cowpeawas planted during autumn seasons of 2009 a factorial experimental design within R.C.B.D with threereplicates was used with two factors. The first factor was the Urea (46%) with three levels (0, 10 and 15kg N/dunam). The second factor was the humic acid with three levels (0, 300 and 600 g / dunam). the result showedthat :( 15kg N/ dunam) and (600 g humic acid / dunam) treatment gave asignificant superiority on the allstudies characterstic (the ratio of protien , carbohydrate content in cowpea seeds tissues , leaves content of (NP-K))and (The mean number of nodules , branches/plant , leaf area and plant height respectively) also ( thepods weight /plant and gave higher total yield (1.77 ton/dunam) (1.52 ton/dunam) respectively) as comparedwith other treatments . Interaction treatments result showed that; (15kg N/ dunam) + (600 g humic acid /dunam) treatment gave asignificant superiority at (the ratio of protein, the mean number of nodules), and for(leaf area as well as branches/plant and plant height) respectively as compared with other treatments. (10kg N/dunam) + (600 g humic acid / dunam) treatment gave asignificant superiority on the other studies charactersticwith( carbohydrate content in cowpea seeds tissues , the pods weight /plant and gave higher total yield (2.35ton/dunam)) , also asignificant leaves content of (N-P-K).